Margaret "Marty" Mann's Public Health Message: Transforming Drunkards into Deserving Patients, 1904-1980 - (:unkn) unknown (My University, 2013)
This study is a biographical history of Margaret "Marty" Mann a unique historical figure who transformed the discussion in America about alcohol in a way that changed public perceptions of people who drank to excess. Mann did not direct the science that established alcoholism as disease, she constructed alcoholism as a democratic disease that could affect anyone, and normalized the alcoholic patient as a person deserving of care. Mann's work contributed to passage of national legislation creating the National Institute on Alcohol Abuse and Alcoholism (NIAAA), the largest funder of alcohol research in the world, enacting her goal to increase knowledge and understanding of alcoholism and remove barriers to treatment for all afflicted. Mann's groundbreaking contribution is a product of her life and her experience that brought attention to women with alcoholism and established sex and gender as important variables in alcohol research.
Keywords: Mann